The scientist as historian: Paulo Vanzolini and the origins of zoology in Brazil O cientista como historiador: Paulo Vanzolini e as origens da zoologia no Brasil - Francisco Inácio Bastos; Magali Romero Sá (História, Ciências, Saúde: Manguinhos)
The Brazilian Paulo Vanzolini is one of the leading herpetologists worldwide. Besides his publications as a zoologist and his activities as a former museum curator and policymaker, Vanzolini pursued a long-life career as a musician and contributed to many different fields such as biostatistics, biogeography and the history of science. The paper analyzes his historical contributions to a key chapter of science in Southern America, the legacy of the so-called traveler naturalists. His analyses comprise major scientists such as Marcgrave, Spix, von Martius, Wied-Neuwied, Castelnau, and Agassiz, are informed by re-analyses of original sources and represent an invaluable repository of historical and scientific information. O brasileiro Paulo Vanzolini é um dos mais importantes herpetologistas do mundo. Além de suas publicações como zoólogo, das atividades de curadoria museológica e de sua atuação na formulação de políticas científicas, Vanzolini tem longa carreira como músico e contribuições a diferentes áreas de conhecimento como bioestatística, biogeografia e história das ciências. O artigo analisa suas contribuições a capítulo fundamental da história das ciências na América do Sul, o legado dos naturalistas viajantes. Suas análises incluem importantes cientistas como Marcgrave, Spix, von Martius, Wied-Neuwied, Castelnau e Agassiz, são feitas a partir da retomada de fontes originais e representam valioso repositório de informações históricas e científicas.